Is There a Crucial Link Between Vitamin D Status and Inflammatory Response in Patients With COVID-19? - Saponaro, Federica; Franzini, Maria; Okoye, Chukwuma; Antognoli, Rachele; Campi, Beatrice; Scalese, Marco; Neri, Tommaso; Carrozzi, Laura; Monzani, Fabio; Zucchi, Riccardo; Celi, Alessandro; Paolicchi, Aldo; et al. (Frontiers in Immunology, 2022)
Background: hypovitaminosis D has been suggested to play a possible role in COVID-19 infection. Methods: the aim of this study is to analyze the relationship between vitamin D status and a biochemical panel of inflammatory markers in a cohort of patients with COVID-19. A secondary endpoint was to evaluate the correlation between 25OHD levels and the severity of the disease. Ninety-three consecutive patients with COVID-19 related pneumonia were evaluated from March to May 2020 in two Hospital Units in Pisa, in whom biochemical inflammatory markers, 25OHD levels, P/F ratio at nadir during hospitalization and complete clinical data were available. Results: 65% of patients presented hypovitaminosis D (25OHD≤20 ng/ml) and showed significantly higher IL-6 [20.8 (10.9-45.6) vs 12.9 (8.7-21.1) pg/ml p=0.02], CRP [10.7 (4.2-19.2) vs 5.9 (1.6-8.1) mg/dl p=0.003], TNFα [8.9 (6.0-14.8) vs 4.4 (1.5-10.6) pg/ml p=0.01], D-dimer [0.53 (0.25-0.72) vs 0.22 (0.17-0.35) mg/l p=0.002] and IL-10 [3.7 (1.8-6.9) vs 2.3 (0.5-5.8) pg/ml p=0.03]. A significant inverse correlation was found between 25OHD and all these markers, even adjusted for age and sex. Hypovitaminosis D was prevalent in patients with severe ARDS, compared to the other groups (75% vs 68% vs 55%, p<0.001) and 25OHD levels were lower in non-survivor patients. Conclusions: The relationship between 25OHD levels and inflammatory markers suggests that vitamin D status needs to be taken in account in these patients’ management. If this is a marker of poor prognosis or a possible risk factors with beneficial effects from supplementation still needs to be elucidated.